PTH-078 Pregnancy outcomes in female patients with inflammatory bowel disease. (22nd June 2015) - Zammit, S Chetcuti; Caruana, M; Katsanos, K; Mantzaris, G; Cesarini, M; Kopylov, U; Zammit, L; Brookes, M; Ellul, P
Abstract : Introduction: Inflammatory Bowel Disease (IBD) typically affects patients during their child-bearing years. With the progress and development of newer IBD treatments patients are increasingly likely to consider having children. The aim of this study was to determine the outcomes of pregnancy in female IBD patients. Method: Female IBD patients were recruited from 5 different centres in Europe. These patients were interviewed through a prospective questionnaire. Results: 233 patients were recruited (mean age 40; SD±11.9). The mean age at diagnosis was 31.4 years (SD±11.2). 85.5% patients had ulcerative colitis (UC). 224 pregnancies were recorded. 26.6% had one pregnancy. 17.2% were pregnant twice, 6.44% were pregnant three times and 1.72% reported 4 pregnancies. 63.8% patients became pregnant before the diagnosis of IBD. A younger age at IBD diagnosis was associated with a higher number of pregnancies (p < 0.006). 1.7% of patients stopped medications on their own accord during pregnancy. Medications were stopped by the doctor in 13.9% (biologic agents in the 3 rd trimester (2.7%), 5-ASA (9.4%), methotrexate (0.9%), prednisolone (0.9%)). Additional medications were used in 3.9% of pregnancies. There were 0.96 live-births/woman recorded. 54.0% of pregnancies were unplanned, with a higher rate in those who were pregnant after being diagnosed with IBD (p < 0.0001). 8.6% of patients reported fertility issues. An IBD exacerbation was reported by 9% of patients during pregnancy. Delivery was by caesarian section in 30.8% and by vaginal delivery in 69.2%. Mode of delivery was influenced by the underlying IBD in 12.0%. Delivery was uncomplicated in the majority of patients (92.0%) with most deliveries between 38 and 40 weeks gestation (81.6%). Mean birth weight was 3.34kg (1.90–4.70kg; SD±0.395). Most newborns (94.6%) were healthy. Other outcomes reported: (1) 0.44% had congenital anomalies (0.44%); (2) 1.34% suffered from developmental delay; (3) 1.75% had low birth weight; (4) 0.89% were born prematurely. One patient (0.44%) suffered a stillbirth. There were no correlations between the use of disease modifying drugs and neonatal adverse outcomes. 29 miscarriages were reported. Only 54.4% of IBD patients breastfed their infants which is less than expected compared to healthy non-IBD pregnancies. Conclusion: Pregnancy outcomes appear to be favourable in IBD compared to European data on non IBD patients. Although there are improvements in the treatment of IBD there still remains a lower birth rate and breast-feeding rate amongst IBD patients when compared to non IBD European data. Disclosure of interest: None Declared.